Editorial Notes: Application of Computational/Artificial Intelligence in Concrete Structures and Materials - Ng, Chee Khoon (UNIMAS Publisher, 2024)
In recent years, the application of computational/artificial intelligence (CI/AI) in concrete structures and materials has gained popularity as evident in the search in the SCOPUS database using these keywords. The integration of CI/AI in concrete structures marks a significant advancement in civil engineering, offering innovative solutions across various stages of infrastructure development. From analysis and design to construction, monitoring, and maintenance, CI/AI technologies revolutionize traditional practices, enabling engineers to optimize concrete structures for enhanced performance, durability, and sustainability. Material design and optimization in concrete have also been propelled forward by CI/AI technologies. Traditional methods rely on trial-and-error, but CI/AI models analyze vast datasets to identify optimal mixtures with superior properties and resistance to environmental factors. Utilization of supplementary cementitious materials and industrial wastes introduces complexities, addressed by CI/AI's predictive capabilities for short- and long-term concrete properties. By minimizing waste and energy consumption, CI/AI-driven design fosters environmentally friendly formulations while ensuring structural integrity. Overall, CI/AI enhances prediction, optimization, and monitoring, ushering in a new era of resilient and sustainable concrete materials. These advancements also contribute to sustainable development by optimizing material usage, reducing waste, and improving energy efficiency, underscoring CI/AI’s transformative potential in shaping the future of concrete structures and materials.